TINJAUAN HUKUM MENGENAI PERLINDUNGAN TENAGA KERJA INDONESIA DIHUBUNGKAN DENGAN PRINSIP STANDAR MIMUM INTERNASIONAL DALAM PERSPEKTIF HAK ASASI MANUSIA - Sumartini, Siti (Universitas Wiralodra, 2018)
Problems of Indonesian Workers (TKI) is never complete, this is caused by many factors that lie behind it. Cases of physical violence, unpaid salaries, sexual ravings to the death penalty of defending. can be drawn a legal issue that focuses as follows; What is the Shape of Protection Against TKIs working in other countries in a human rights perspective? and How can the International Minimum Standards Principle be applied as a form of protection to labor migrants?. This research is done by using normative juridical method. This juridical approach is due to this research by analyzing the legal aspects that exist, and is normative since this study focuses more on the analysis of existing legislation and other regulations, both from national and international perspectives, as well as using data secondary data that is scientific references or other scientific writings as a study material that can support the completeness of this scientific work. Legal protection regarding TKI is an absolute must be done by the Indonesian government, given the TKI is a foreign exchange hero for the country.